Successful pregnancy in morbidly obese lady with polycystic ovary syndrome after bariatric surgery: A case report - Dg Marshitah Pg Baharuddin; Nang Kham Oo Leik; Mohd Firdaus Mohd Hayati; Mohd Nazri Mohd Daud; Edwin See; Siti Zubaidah Sharif; Nik Amin Sahid Nik Lah (Elsevier, 2021)
Introduction: Obesity has been proven to have adverse effects on fertility and is one of the predisposing factors for delay in pregnancy even with the use of assisted reproductive technique. There are many pathways in which obesity can affect fertility such as anovulation, poor implantation and low-quality oocyte. Case presentation: We report a case of a 40-year-old lady with primary infertility for six years with underlying polycystic ovary syndrome (PCOS) and BMI 45.7 whom was successfully conceived twice following bariatric surgery procedure in which reduction of 70% of her BMI prior to bariatric surgery lead to her spontaneous conception without fertility intervention and successful live birth. Clinical discussion: Obese PCOS needs multidisciplinary approaches which include weight loss program such as dietary advice, exercise intervention as part of preliminary treatment prior to ovulation induction and counselling. Conclusion: Bariatric surgery has been a mainstay treatment in patients with morbid obesity and those with BMI more than 35 associated with obesity related problems such as joint pain, hypertension or diabetes mellitus. Bariatric surgery such as laparoscopic sleeve gastrectomy should be considered more often in contrast to lifestyle modification for morbidly obese lady with PCOS and infertility prior to the use of standard ovulation induction regime for treating infertility.